Aryltrifluoromethylative cyclization of unactivated alkenes by the use of PhICF3Cl under catalyst-free conditions. Issue 8 (5th February 2019) - Guo, Jia; Xu, Cong; Liu, Xiaowei; Wang, Mang
Abstract : A concise and catalyst-free aryltrifluoromethylative cyclization of unactivated alkenes has been developed herein. Abstract : A concise and catalyst-free aryltrifluoromethylative cyclization of unactivated alkenes has been developed herein. The use of PhICF3 Cl as a powerful trifluoromethylating agent allows easy transformations. A set of trifluoroethylated carbocycles and aza-hereocycles were efficiently synthesized in good yield and selectivity. A broad substrate scope, mild reaction conditions, and easy operation would make this method well-suited for applications.